Analisis Problematika Guru dalam Pembelajaran Arab Melayu di SDN 008 Sungai Simbar - Wiratama, Rivaldi; Sapriani, Reskika (Awwaliyah: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2024)
This study aims to describe various problems in Malay Arabic learning and provide alternative solutions. SDN 008 Sungai Simbar is where the research was conducted with informants totaling 6 class teachers. Interviews and documentation are selected as data collection techniques which are then analyzed through data reduction, data presentation, and conclusion formulation. Research shows problems in learning Arabic Malay  at SDN 008 Sungai Simbar include, (1) learning media, (2) variations of teaching materials, (3) learning methods, (4) short time allocation, (5) learning evaluation, and (6) internal student factors. Solutions that teachers can do are Utilizing objects around school and class, using appropriate learning methods, using the internet and collaborating with colleagues, using teaching modules as learning references, using simple and interesting evaluation instruments. If these four problems can be solved, then the problem of students' internal factors will also be solved.